Rural adolescent health: Issues, behaviors and self-reported awareness - Jacobs, Molly (Journal of Community Medicine and Health Solutions, 2020)
Purpose: The purpose of the study was to examine the health status of rural adolescents and young adults in the United States through a comprehensive review of detailed health information, behavior and health awareness. The disparity in health awareness between rural and non-rural residents compared and evaluated. Methods: Rural-Urban Commuting Area (RUCA) codes were combined with respondent-level data from the Longitudinal Survey of Adolescent to Adult Health (Add Health) to classify individuals as rural/non-rural residents. Health characteristics and perceived health awareness was tested for statistically significant differences using ANOVA. Differences in weight perception accuracy was compared for systematic differences controlling for self-selection into rural areas using a two-stage logistic selection model. Findings: Analysis revealed that rural residents have a higher incidence of major health conditions including epilepsy, high cholesterol, high blood pressure and diabetes. Additionally, they have a higher prevalence of unhealthy behaviors including drinking and drug use. Rural residents are less likely to be insured, but more likely to be overweight or obese. While rural adolescents are more likely to mis-classify their body weight, this misclassification is a result of the higher incidence of overweight rather than the residential location. Conclusion: The higher prevalence of chronic conditions combined with the income and education levels suggests the rural environment is a unique and potentially challenging context for adolescent health. Improving rural adolescent health will require innovative solutions appropriate for rural environments and changes in individual health literacy. Solutions must be multisectoral, engaging education, economic development, and other community perspectives to establish key drivers for health equity.